Comparison of transperineal ultrasound image guidance technique to transabdominal technique for prostate radiation therapy. Issue 12 (27th October 2020) - Szegedi, Martin; Boehm, Christine; Paxton, Adam; Rassiah‐Szegedi, Prema; Sarkar, Vikren; Zhao, Hui; Su, Frances; Kokeny, Kristine E.; Lloyd, Shane; Tward, Jonathan; Salter, Bill J.
Abstract : Introduction: Ultrasound (US) guidance of the prostate has long been conducted using a transabdominal (TA) approach. More recently, a transperineal (TP) approach has been made available for image guidance. Our aim was to determine if both methods produced similar alignments within the same patients. Materials and methods: We utilized two clinical US image guidance (IG) systems (Elekta Clarity and Best B AT). The B‐mode Acquisition and Targeting USIG system is a bi‐planar, so‐called 2.5D USIG system, that is acquired TA. Clarity is a 3D US system that generates a volumetric 3D US data set and US‐derived IG contours that are coregistered to the planning CT images. The probe is oriented in the sagittal plane against the perineum (TP). After positioning the patient for treatment using the TP USIG, we maintained the position defined by Clarity tracking and then acquired a TA‐based USIG. The two US‐based methods of localizing the prostate (TA vs TP) were compared via Bland–Altman (BA) statistical analysis to determine if there was alignment agreement between methods. Results: The BA test for all 101 patients, 2093 fractions resulted in 95% confidence intervals (upper and lower limits of the BA test) of 0.6 mm in LR, 0.9 mm in AP and 1.0 mm in SI. The bias between the two systems was calculated as 0.03, 0.02, and 0.03 mm in LR, AP, and SI. Conclusions: Both systems resulted in statistically equivalent targeting positions for the prostate. Because of the unique intrafraction, real‐time motion tracking capability of the TP system, this solution represents a unique extension to the previously reported clinical benefits of a TA approach by providing assurance of the prostate remaining in the treatment field during beam‐on.